PENGEMBANGAN WEBSITE KARAKTER KARIR DALAM MENINGKATKAN PEMAHAMAN KARIR SISWA (Studi RnD Pada Siswa Kelas X SMAN 6 KOTA SERANG Tahun Ajaran 2020/2021) - Laila Hanifah; Bangun Yoga Wibowo; Arga Satrio Prabowo (SISTEMA: Jurnal Pendidikan, 2022)
This research was conducted aiming to develop a website-based learning media that is useful in the use of guidance implementation and makes it easier for students to get information about careers easily. The research method used is Research and Development (R&D). The research subjects were selected through sampling on students using a purposive technique which in the end obtained students who matched the needs of the sample, namely the lack of students in understanding careers. Data analysis used quantitative data analysis which was then analyzed descriptively. The results of the research that have been carried out have received an assessment of 95.4% from material experts and 98.4% from media experts. In the pretest, 9 students were obtained, then the treatment and posttest were carried out afterwards, the average result was a 28% increase in career understanding. It can be concluded that website-based learning media regarding career information can help students in increasing students' career understanding